Radiological impact of phosphogypsum surface application in a no-till system in Southern Brazil - Dias, Nivea Maria Piccolomini; Caires, Eduardo Fávero; Pires, Luiz Fernando; Bacchi, Márcio Arruda; Fernandes, Elisabete Aparecida De Nadai (Pesquisa Agropecuaria Brasileira, 2011)
The objective of this work was to determine the impact of phosphogypsum application on 226Ra and 228Ra activities in the soil and on their accumulation in soybean grains. A field experiment was carried out in Paraná state, Brazil, on a loamy Typic Hapludox, under no-till system, with increasing phosphogypsum rates: 4, 8, and 12 Mg ha-1. Gamma-ray spectrometry was carried out using HPGe detectors with 45 and 10% relative efficiencies, for soybean grains and soil, respectively. No increment of 226Ra and 228Ra activities was observed due to the increase in phosphogypsum rates in the soil, and a small reduction was noticed in the grains. Average values found for 226Ra and 228Ra activities were 37 and 57 Bq kg-1 in the soil and 1.44 and 3.19 Bq kg-1 in soybean grains. The application of phosphogypsum for no-till soybean production is a safe practice regarding the risks of radiation damage to human health.